ANALISIS PERKEMBANGAN INDUSTRIALISASI ERA 5.0 TERHADAP KONDISI PENDIDIKAN DI KECAMATAN MENGANTI KABUPATEN GRESIK JAWA TIMUR - Yordan Rendis Suherman; Tangkas Ageng Nugroho; Fitra Barokah Quraini; Muhammad Yasin (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to describe the development of industry 5.0. In addition, the researchers also described the education sector in Menganti District, Gresik Regency - East Java during the industrial era 5.0. The scope of this research is the development of industrialization in the 5.0 era in educational activities in Menganti District, Gresik Regency - East Java. This study uses a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that basically the industrial revolution and society 5.0 are able to improve the quality of human life. The implementation of learning in Menganti District seeks to improve the quality of human resources to be technologically literate and think critically about a problem. This is applied by the majority of teachers with various appropriate learning methods or strategies. The implementation of education in Menganti District has also used various technologies to make it easier for students to understand lessons. This is in line with Industry 5.0 which focuses on the use of technology in life which can improve the quality of human resources and facilitate the activities carried out by the surrounding community.